N, P, S, Mn quaternary co-doped carbon-based catalyst, and preparation method and application thereof
Patent Information
- Application Number
- CN202611110791.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-20
AI Technical Summary
然而,目前公开报道的杂原子掺杂碳基催化剂主要集中于单一元素或双元素掺杂,对于N、P、S、Mn四种杂原子协同共掺杂的碳基催化剂及其在棕榈油废水脱色中的应用尚未见报道
[0029](1)本发明多杂原子协同效应显著:N、P、S、Mn四种杂原子共掺杂产生协同效应,形成多种类型的活性位点(C-N、C-P、C-S、原子级Mn、C-N-P-S-Mn复合位点等),即使在Mn含量较低(0.1%~0.3%)的情况下,也能有效提升催化剂活化臭氧的能力和效率。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of advanced industrial wastewater treatment technology, specifically relating to a quaternary co-doped carbon-based catalyst of N, P, S, and Mn, its preparation method, and its application. Background Technology
[0002] Palm oil is one of the world's three major vegetable oils, with an annual production exceeding 70 million tons. The processing of palm oil, including pressing, refining, and deodorization, generates large amounts of high-concentration organic wastewater. This wastewater is characterized by high color (dark reddish-brown), high chemical oxygen demand (COD), high oil content, complex composition, and poor biodegradability. The main pigment components in the wastewater include carotenoids (such as β-carotene, α-carotene, lutein, and zeaxanthin), chlorophyll and its degradation products, and flavonoids. These substances have complex conjugated double bond structures, are chemically stable, and are difficult to decolorize effectively using conventional treatment methods.
[0003] Currently, the main technologies for decolorizing palm oil wastewater include: (1) Coagulation and sedimentation: using coagulants such as aluminum salts and iron salts to destabilize and coagulate pigment colloids, but the effect of removing soluble pigments is poor and a large amount of metal-containing sludge is generated; (2) Adsorption: using adsorbents such as activated carbon and bentonite to remove pigments, but the adsorption capacity is limited, the adsorbent regeneration is difficult, and the operating cost is high; (3) Biological method: using microorganisms to degrade pigments, but the pigment molecular structure is complex, the biodegradation rate is slow, and the treatment cycle is long; (4) Chemical oxidation method: including Fenton oxidation, ozone oxidation, etc., which can effectively destroy the pigment chromophores, but there are problems such as difficulty in catalyst recovery, generation of iron sludge, and low ozone utilization rate; (5) Membrane separation method: there are problems of membrane fouling and concentrated liquid treatment.
[0004] Heterogeneous catalytic ozone oxidation technology utilizes catalysts to promote the decomposition of ozone, generating more potent hydroxyl radicals (·OH, E0=2.80V). These radicals can non-selectively attack organic pollutants in wastewater, achieving efficient decolorization and organic matter degradation. Carbon-based materials are widely used as catalyst supports for ozone catalytic oxidation due to their abundant resources, strong chemical stability, and easily tunable surface properties. However, unmodified carbon-based catalysts exhibit low efficiency in catalytic ozone oxidation due to the limited number of surface active sites.
[0005] In recent years, heteroatom doping has proven to be an effective strategy for improving the catalytic performance of carbon-based materials. Studies have shown that heteroatom doping can effectively regulate the electronic structure and surface properties of carbon materials, creating more active sites. Nitrogen (N) doping can introduce active configurations such as pyridine nitrogen and pyrrole nitrogen, enhancing the basicity and electron donor ability of carbon materials; phosphorus (P) doping can expand the carbon interlayer spacing and increase defect sites; sulfur (S) doping can regulate the electron cloud distribution of carbon materials, enhancing their adsorption and activation capabilities for oxidants; transition metal manganese (Mn) possesses multivalent state characteristics (Mn... 2+ / Mn 3+ / Mn 4+ Carbon-based catalysts, especially those doped with N, P, S, and Mn, are excellent active components for activating oxidants. However, currently reported heteroatom-doped carbon-based catalysts mainly focus on single-element or dual-element doping, and there are no reports on carbon-based catalysts with synergistic co-doping of N, P, S, and Mn heteroatoms and their application in palm oil wastewater decolorization.
[0006] In the prior art, Chinese patent CN119869236A discloses a method for preparing a metal-doped carbon-nitrogen polymer, but the metal-doped carbon-nitrogen polymer prepared by hydrothermal calcination technology is mainly for membrane fouling self-cleaning applications and does not involve the field of wastewater treatment. Chinese patent CN120885253A discloses a multi-metal carbon-based catalyst modified by N and P co-doping and its preparation method, which only involves N and P dual-element doping and is applied to the treatment of leachate from aged landfills, without addressing the decolorization problem of palm oil wastewater. In addition, none of the above-mentioned prior art discloses a carbon-based catalyst system containing four heteroatoms: N, P, S, and Mn, nor does it reveal the synergistic effect of the four heteroatoms in ozone catalytic oxidation and the Mn-SC and PN synergistic active centers formed therein. Furthermore, there are no reports in the prior art of using the N, P, and S elements contained in palm oil processing waste (such as empty palm fruit bunches) as endogenous heteroatom precursors to prepare ozone catalysts. Summary of the Invention
[0007] The first technical problem solved by this invention is to provide a quaternary co-doped carbon-based catalyst of N, P, S, and Mn. This catalyst exhibits a synergistic effect among the heteroatoms, forming a CNPS-Mn composite active center, significantly reducing the activation energy and improving catalytic efficiency. This quaternary synergistic mechanism enables the catalyst of this invention to exhibit catalytic efficiency far superior to single-doped or dual-doped systems in ozone catalytic oxidation. The second technical problem solved by this invention is to provide a method for preparing the quaternary co-doped carbon-based catalyst of N, P, S, and Mn. This method employs a one-step high-temperature co-pyrolysis method to simultaneously introduce the four heteroatoms N, P, S, and Mn into the carbon framework. The process is simple, easy to scale up, and suitable for industrial applications. The third technical problem solved by this invention is to provide the application of this catalyst in the ozone catalytic oxidation deep decolorization treatment of palm oil wastewater.
[0008] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing an N, P, S, Mn quaternary co-doped carbon-based catalyst includes the following steps:
[0010] (1) The porous carbon material was washed, dried, and calcined to obtain carbon precursor powder;
[0011] (2) Dissolve the carbon precursor powder with nitrogen, phosphorus, sulfur and manganese sources in deionized water, disperse by ultrasonication and impregnate in water bath;
[0012] (3) The mixture was subjected to a hydrothermal reaction and dried to obtain a precursor / carbon composite material;
[0013] (4) The precursor / carbon composite material obtained in step (3) is calcined in an inert atmosphere, washed and dried to obtain a quaternary co-doped carbon-based catalyst.
[0014] Further, in step (1), the porous carbon material is selected from one or more of coconut shells, hollow palm fruit bunches, straw, bamboo shavings, peanut shells, sugarcane bagasse, and sawdust.
[0015] Further, in step (2), the nitrogen source is selected from one or more of urea, melamine, dicyandiamide, and ammonium nitrate; the phosphorus source is selected from one or more of phosphoric acid, phytic acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; the sulfur source is selected from one or more of thiourea, sodium thiosulfate, and benzenesulfonic acid; and the manganese source is selected from one or more of manganese nitrate, manganese acetate, manganese chloride, manganese sulfate, potassium permanganate, and manganese acetylacetone.
[0016] Furthermore, in step (2), the mass ratio of nitrogen source, phosphorus source, sulfur source and manganese source is 2~5:5~10:3~8:0.1~1.
[0017] Furthermore, in step (2), the water bath temperature is 50~70℃ and the time is 4~6h.
[0018] Furthermore, in step (3), the hydrothermal reaction temperature is 160~180℃ and the hydrothermal reaction time is 7~9h.
[0019] Furthermore, in step (4), the calcination temperature is 750~850℃, the heating rate is 5~8℃ / min, and the calcination time is 1.5~2.5h.
[0020] Furthermore, the method described above for preparing N, P, S, Mn quaternary co-doped carbon-based catalysts yields N, P, S, Mn quaternary co-doped carbon-based catalysts.
[0021] Furthermore, the application of the quaternary co-doped carbon-based catalyst in the ozone catalytic oxidation deep decolorization treatment of palm oil wastewater.
[0022] Furthermore, the catalyst dosage is 0.5~1.5 g / L, the ozone dosage is 50~150 mg / L, the reaction time is 30~90 min, and the reaction pH is 6.0~9.0.
[0023] The core mechanism by which the catalyst exhibits excellent performance in palm oil wastewater decolorization lies in the synergistic catalytic effect of four heteroatoms:
[0024] (1) N and P co-doping: can promote electron delocalization on the surface of carbon-based catalysts, form regional polar sites, and reduce the energy barrier for the generation of hydroxyl radicals (·OH). N doping (especially pyridine N and pyrrole N) enhances the activity of sp² carbon lattice by increasing surface electronegativity, thereby strengthening the adsorption and activation of ozone molecules; P doping can further reshape the electron distribution on the carbon surface, stabilize active sites, and produce a synergistic enhancement effect with N.
[0025] (2) Dual regulation of S element: The introduction of S element produces two unique enhancement effects. First, S doping introduces sulfur functional groups (such as -CSC-, -C=S, etc.) into the carbon lattice. These functional groups can act as electron donors to accelerate electron transfer in the ozone decomposition process. Second, S element forms a special electronic coupling structure with other heteroatoms (especially N and P), generating cooperative polar sites, which further enhances the affinity of the catalyst surface for ozone and organic pollutant molecules.
[0026] (3) Catalytic activation by Mn: Mn doping provides Lewis acidic sites for the catalyst. Studies have shown that Mn in MnOx catalysts... 3+ Closely related to surface oxygen vacancies, which are active sites for ozone decomposition, the introduction of Mn into the carbon framework allows Mn species to be embedded in the carbon matrix in a highly dispersed form. This effectively catalyzes the decomposition of ozone to generate ·OH while preventing the agglomeration and deactivation of metal particles.
[0027] (4) Synergistic Effect of Four Elements: More importantly, the four heteroatoms N, P, S, and Mn do not function independently in the carbon framework, but rather produce a significant synergistic effect through complex electronic interactions. Specifically, the electron delocalization structure constructed by N / P co-doping provides a more favorable electronic environment for S and Mn; the electron donor effect of S enhances the catalytic activity of Mn sites; and the Lewis acid sites of Mn further promote the adsorption and activation of ozone in the electron-rich region. The synergistic effect among the heteroatoms forms a CNPS-Mn composite active center, significantly reducing the activation energy and improving the catalytic efficiency. This quaternary synergistic mechanism enables the catalyst of this invention to exhibit a catalytic efficiency far superior to that of single-doped or double-doped systems in ozone catalytic oxidation.
[0028] Compared with the prior art, the present invention has the following advantages:
[0029] (1) The present invention has a significant synergistic effect of multiple heteroatoms: co-doping of four heteroatoms, N, P, S and Mn, produces a synergistic effect and forms a variety of active sites (CN, CP, CS, atomic-level Mn, CNPS-Mn composite sites, etc.). Even when the Mn content is low (0.1%~0.3%), it can effectively improve the catalyst’s ability and efficiency to activate ozone.
[0030] (2) The catalyst prepared by the present invention has excellent catalytic degradation performance for carotenoids, chlorophyll and other difficult-to-degrade colored organic matter in palm oil wastewater. The color removal rate can reach more than 95% and the COD removal rate can reach more than 50%, which is significantly better than single or double heteroatom doped catalysts.
[0031] (3) This invention employs a one-step high-temperature co-thermolysis method to simultaneously introduce four heteroatoms—N, P, S, and Mn—into the carbon framework. The process is simple, easy to scale up, and suitable for industrial applications. This invention uses biomass waste (such as coconut shells, empty palm fruit bunches, and straw) as the carbon source and common chemical raw materials as heteroatom precursors. The raw material sources are wide-ranging and conform to the concepts of green chemistry and circular economy.
[0032] (4) The heteroatoms of the present invention are stably doped into the carbon framework in the form of chemical bonds, and there is a strong interaction between the Mn component and the carbon support. The catalyst maintains stable activity after multiple cycles of use, which reduces operating costs. At the same time, the catalyst itself does not contain toxic components, does not generate secondary pollution during the reaction, and the catalyst is easy to separate and recover after the reaction, which meets environmental protection requirements.
[0033] (5) The catalyst prepared by this invention exhibits good catalytic activity in the pH range of 4 to 9, adapting to the pH fluctuations of palm oil wastewater. Moreover, the Mn content in the catalyst is only 0.1% to 0.3%, which is much lower than that of traditional manganese-based catalysts (usually >5%), significantly reducing the catalyst preparation cost and avoiding the environmental risks that may be caused by high manganese content. Attached Figure Description
[0034] Figure 1 SEM image of the N, P, S, Mn multi-heteroatom co-doped carbon-based catalyst prepared in Example 1 of this application;
[0035] Figure 2 EDS surface scan image of the N, P, S, Mn multi-heteroatom co-doped carbon-based catalyst prepared in Example 1 of this application;
[0036] Figure 3 The image shows the EDS quantitative analysis results of the N, P, S, Mn multi-heteroatom co-doped carbon-based catalyst prepared in Example 1 of this application.
[0037] Figure 4 The FTIR spectrum of the N, P, S, Mn multi-heteroatom co-doped carbon-based catalyst prepared in Example 1 of this application is shown.
[0038] Figure 5 The Raman spectra of the carbon-based catalysts prepared from the catalysts prepared in Examples 1, 1, 3, and 4 of this application are shown. Detailed Implementation
[0039] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention. Where specific techniques or conditions are not specified in the embodiments, operation should be performed according to the techniques or conditions described in the literature in this field, or according to the product instructions. Reagents or instruments used without specified manufacturers are all commercially available conventional products.
[0040] Example 1
[0041] A method for preparing an N, P, S, Mn quaternary co-doped carbon-based catalyst includes the following steps:
[0042] (1) Take fresh coconut shells, wash them with deionized water, and dry them at 105℃ to constant weight. Place the dried coconut shells in a tube furnace and heat them to 500℃ at 5℃ / min under N2 protection, and keep them at that temperature for 2 hours for pre-carbonization. After cooling, crush the pre-carbonized product and pass it through a 150-mesh sieve to obtain coconut shell carbon precursor powder.
[0043] (2) Weigh 10.0g of coconut shell carbon precursor powder, 4.5g of phosphoric acid (85wt%), 3.0g of thiourea, 2.5g of urea and 0.5g of manganese nitrate (Mn(NO3)2·4H2O) and dissolve them in 50mL of deionized water. Disperse the mixture by sonication for 2h to ensure that all components are thoroughly mixed and homogeneous. Stir and soak the mixture in a 60℃ water bath for 6h. The mass ratio of nitrogen source (urea), phosphorus source (phosphoric acid), sulfur source (thiourea) and manganese source (manganese nitrate) is 2.5:4.5:3.0:0.5.
[0044] (3) Transfer the entire mixture obtained in step (2) into a 200 mL polytetrafluoroethylene-lined hydrothermal reactor, seal it, and place it in an oven for hydrothermal reaction at 170 °C for 8 h. After the reaction is complete, allow it to cool naturally to room temperature, remove the hydrothermal product, and dry it in an oven at 105 °C for 8 h to obtain the precursor / carbon composite material.
[0045] (4) The dried precursor / carbon composite material was placed in a tube furnace and heated to 800°C at a heating rate of 5°C / min under nitrogen atmosphere protection, and pyrolyzed at a constant temperature for 2 hours. After pyrolysis, it was naturally cooled to room temperature, the product was taken out, washed repeatedly with deionized water until neutral, and dried at 105°C for 6 hours to obtain a carbon-based catalyst co-doped with N, P, S and Mn heteroatoms.
[0046] Depend on Figure 1 Scanning electron microscopy (SEM) images of the N, P, S, and Mn multi-heteroatom co-doped carbon-based catalyst prepared in Example 1 show that the catalyst surface retains the rich microporous structure of the original activated carbon, and no obvious metal oxide agglomerates were observed, indicating that Mn species are highly dispersed in the carbon framework. Figure 2 The EDS surface scan results show that the five elements C, N, P, S and Mn exhibit a highly uniform distribution at the micrometer scale, with no local enrichment regions. This proves that the four heteroatoms have been uniformly doped into the carbon matrix, rather than being a simple physical mixture or surface deposition.
[0047] Depend on Figure 3 The EDS quantitative analysis results of the N, P, S, Mn multi-heteroatom co-doped carbon-based catalyst prepared in Example 1 show that the mass percentage of each element in the catalyst is: C 82.3%, O 5.2%, P 4.9%, S 3.4%, N 1.6%, Mn 0.17%, with the balance being other trace elements.
[0048] Depend on Figure 4 Fourier transform infrared (FTIR) spectra of the N, P, S, Mn multi-heteroatom co-doped carbon-based catalyst prepared in Example 1 show that the quaternary doped catalyst exhibits high performance at 1180 cm⁻¹. -1 A CS stretching vibration peak appears at 1050 cm⁻¹. -1A POC vibration peak appears at 1405 cm⁻¹. -1 A CN stretching vibration peak appears at 500-600 cm⁻¹, and also at 500-600 cm⁻¹. -1 The region exhibits characteristic Mn-O / Mn-S absorption bands. These characteristic peaks are absent in undoped activated carbon and only partially appear in single-doped or double-doped samples. The simultaneous presence of multiple heteroatoms (CS, POC, CN, and Mn-S) in the quaternary doped sample directly demonstrates that the four heteroatoms (N, P, S, and Mn) are successfully anchored to the carbon framework surface via covalent bonds, forming a rich network of surface functional groups.
[0049] Example 2
[0050] A method for preparing an N, P, S, Mn quaternary co-doped carbon-based catalyst includes the following steps:
[0051] The difference from Example 1 is that in step (2), 3.5g of phytic acid (50wt%), 2.5g of sodium thiosulfate, 3.0g of melamine and 0.3g of manganese acetate (Mn(CH3COO)2·4H2O) are weighed.
[0052] In step (3), the hydrothermal reaction temperature is 160℃ and the reaction time is 10h;
[0053] In step (4), the pyrolysis temperature is 750℃ and the pyrolysis is carried out at a constant temperature for 2.5h.
[0054] The obtained catalyst, analyzed by EDS, contained 3.8% P, 2.9% S, 1.8% N, and 0.12% Mn.
[0055] Example 3
[0056] A method for preparing an N, P, S, Mn quaternary co-doped carbon-based catalyst includes the following steps:
[0057] The difference from Example 1 is that in step (1), fresh coconut shells are replaced with peanut shells (the specific surface area of the carbon precursor is 880 m² / g).
[0058] The obtained catalyst, analyzed by EDS, contained 4.5% P, 3.1% S, 1.5% N, and 0.15% Mn.
[0059] Comparative Example 1 (ternary doped, lacking S)
[0060] The difference from Example 1 is that in step (2), no sulfur source (thiourea) is added. That is, the nitrogen source (urea), phosphorus source (phosphate), and manganese source (manganese nitrate) are added to deionized water in the same amounts as in Example 1, and the remaining steps are exactly the same as in Example 1. The obtained catalyst was analyzed by EDS, and no sulfur element was detected. P, N, and Mn elements were all successfully doped.
[0061] Comparative Example 2 (ternary doped, lacking Mn)
[0062] The difference from Example 1 is that in step (2), no manganese source (manganese nitrate) is added. Instead, the nitrogen source (urea), phosphorus source (phosphate), and sulfur source (thiourea) are added to deionized water in the same amounts as in Example 1. The remaining steps are exactly the same as in Example 1. The obtained catalyst was analyzed by EDS, and no Mn element was detected. P, S, and N elements were all successfully doped.
[0063] Comparative Example 3 (Binary doping, lacking S and Mn)
[0064] The difference from Example 1 is that in step (2), no manganese source (manganese nitrate) and sulfur source (thiourea) are added; that is, only nitrogen source (urea) and phosphorus source (phosphoric acid) are added. The remaining steps are exactly the same as in Example 1. The obtained catalyst was analyzed by EDS, and no Mn and S elements were detected. P and N elements were successfully doped.
[0065] Comparative Example 4 (Undoped carbon material)
[0066] Fresh coconut shells were taken, washed clean with deionized water, and dried at 105℃ to constant weight. The dried coconut shells were placed in a tube furnace and pre-carbonized at 500℃ under N2 protection at a rate of 5℃ / min for 2 hours. After cooling, the pre-carbonized product was pulverized and passed through a 150-mesh sieve to obtain coconut shell carbon precursor powder.
[0067] Comparative Example 5 (Commercial Catalyst)
[0068] A commercially available ozone catalytic oxidation catalyst (alumina-based supported multi-metal catalyst).
[0069] Raman spectroscopy analysis was performed on the catalysts prepared in Example 1, Comparative Example 1, Comparative Example 3, and Comparative Example 4. The results are shown in Table 1 and 2. Figure 5 .
[0070] Table 1. Raman spectral data of different catalysts
[0071]
[0072] Depend on Figure 5 As shown in Table 1, the intensity ratio of the D peak to the G peak of undoped activated carbon (Comparative Example 4) is (I D / I GThe value of I0.84 for the binary doped catalyst (Comparative Example 3, NP) was 0.84. D / I G The value is 0.93; the I value of the ternary doped catalyst (Comparative Example 1, NP-Mn) is... D / I G The value increased to 1.05; while the I of the quaternary doped catalyst (Example 1, NPS-Mn) was... D / I G The value is as high as 1.12. D / I G The gradual increase in the value indicates that the density of structural defects and edge sites introduced into the carbon lattice increases with the increase in the types of doping elements. The quaternary doped sample has the highest defect density. These defect sites are rich in unpaired π electrons, which can serve as active centers for the adsorption and activation of ozone molecules. This explains the intrinsic reason why the catalytic activity of the quaternary doped system is significantly better than that of the low-element doped system from the perspective of carbon framework structure.
[0073] Application examples
[0074] I. Deep Decolorization Test of Palm Oil Wastewater by Ozone Catalytic Oxidation
[0075] Wastewater from a palm oil processing plant, after anaerobic-aerobic biological treatment, was used as the test water sample. The water quality characteristics were: color 1800 times, COD 380 mg / L, pH 7.2. Ozone catalytic oxidation decolorization experiments were conducted using catalysts prepared in Examples 1-3 and Comparative Examples 1-5, respectively. Experimental conditions: catalyst dosage 1.0 g / L, ozone dosage 120 mg / L, reaction time 60 min, reaction temperature 25℃, using a batch reactor, and magnetic stirring speed 200 rpm. After the reaction, samples were taken to measure color and COD. The experimental results are shown in Table 2 below.
[0076] Table 2 Ozone catalytic oxidation decolorization test with different catalysts
[0077]
[0078] As shown in Table 2:
[0079] (1) The N, P, S and Mn quaternary co-doped catalyst prepared in Example 1 achieved a color removal rate of up to 95.2% and a COD removal rate of 65.8% for palm oil wastewater, which was significantly better than all comparative examples.
[0080] (2) The decolorization effects of Comparative Example 1 (NP-Mn, without S) and Comparative Example 2 (NPS, without Mn) were significantly lower than those of Example 1, at only 78.3% and 82.5%, respectively, proving that both S and Mn elements make substantial contributions to the catalyst performance. The absence of S led to a decrease in the color removal rate of about 17 percentage points, and the absence of Mn led to a decrease in the color removal rate of about 13 percentage points. Both elements have an irreplaceable enhancing effect on the catalytic performance.
[0081] (3) The color removal rate of Example 1 was increased by 18.8 percentage points compared with Comparative Example 3 (NP binary doping), by 32.5 percentage points compared with Comparative Example 4 (undoped activated carbon), and by 43.8 percentage points compared with ozone alone (blank control), which fully demonstrates the significant enhancing effect of N, P, S, Mn quaternary co-doping on catalytic activity. As the doping element gradually increases from binary to ternary to quaternary, the decolorization performance shows a step-by-step improvement trend, reflecting the synergistic enhancement effect of the four elements.
[0082] (4) The decolorization effect of Example 1 is significantly better than that of commercial ozone catalyst (Comparative Example 5), indicating that the catalyst of the present invention has a strong competitive advantage in practical applications.
[0083] II. Effect of Catalyst Dosage
[0084] Under the condition that other conditions remain unchanged (palm oil wastewater: color 1800 times, COD 380 mg / L, pH 7.2; ozone dosage 120 mg / L; reaction time 60 min), the effect of the dosage of the catalyst prepared in Example 1 on the decolorization effect of palm oil wastewater was investigated, and the results are shown in Table 3.
[0085] Table 3. Effects of different catalyst dosages on the decolorization effect of palm oil wastewater
[0086]
[0087] Table 3 shows that excellent decolorization effect can be achieved when the catalyst dosage is 0.5 g / L, and the improvement in removal rate gradually decreases with further increasing the dosage. Considering both treatment effect and economy, the optimal catalyst dosage is 0.5~1.0 g / L.
[0088] III. The Effect of Solution pH
[0089] Under the condition that other factors remain unchanged, the effect of initial pH of the solution on the decolorization effect was investigated for palm oil wastewater with a color of 1800 times, COD of 380 mg / L, catalyst dosage of 1.0 g / L, ozone dosage of 120 mg / L, and reaction time of 60 min. The results are shown in Table 4.
[0090] Table 4. Effect of initial pH of different solutions on decolorization effect
[0091]
[0092] As shown in Table 4, the catalyst prepared in Example 1 of this application exhibits good catalytic activity within a pH range of 4-9, with color removal rates all above 88%, indicating that the catalyst of this invention has a wide applicable pH range. Among these, the decolorization effect is optimal within a pH range of 5-8 (color removal rate ≥94%), which closely matches the actual pH range of palm oil wastewater effluent (typically 6.5-8.5). This allows for direct application without significant pH adjustment, reducing the consumption of acid and alkali reagents and lowering operating costs.
[0093] IV. The Influence of Different Manganese Sources
[0094] The difference from Example 1 is that in step (2), manganese nitrate is replaced with equimolar amounts of manganese acetate, potassium permanganate, and manganese acetylacetone, respectively. The remaining steps are exactly the same as in Example 1, and quaternary co-doped carbon-based catalysts with different manganese sources are prepared. They are applied to the ozone catalytic oxidation deep decolorization test of palm oil wastewater (the test conditions are the same as in Application Example 1), and the results are shown in Table 5.
[0095] Table 5. Effects of different manganese source catalysts on decolorization effect
[0096]
[0097] Table 5 shows that the catalyst performance is better when manganese acetate or manganese acetylacetonate is used as the manganese source. This is because manganese nitrate and manganese acetylacetonate decompose more uniformly during pyrolysis, which is conducive to the formation of atomically dispersed Mn sites, thereby providing more Lewis acidic sites for ozone activation.
[0098] V. Catalyst stability test
[0099] The catalyst prepared in Example 1 was subjected to five cycles of use under the same conditions. After each reaction, the catalyst was recovered, washed with deionized water, dried, and reused. The results are shown in Table 6.
[0100] Table 6 Catalyst Recycling Performance
[0101]
[0102] Table 6 shows that the color removal rate remained above 91% after 5 cycles, indicating that the catalyst has good stability and reusability. Analysis of the Mn content in the reaction solution after recycling revealed... 2+ The leaching concentration is less than 0.05 mg / L, which proves that the Mn element is firmly locked in the carbon skeleton and will not cause secondary pollution.
[0103] VI. Adaptability Tests for Different Initial Wastewater Conditions
[0104] The catalyst from Example 1 was used in ozone catalytic oxidation experiments under the conditions described above in palm oil biochemical wastewater with different initial color values (1200~3500 times) and different initial CODs (250~550 mg / L). The results are shown in Table 7.
[0105] Table 7 Decolorization effect under different initial wastewater conditions
[0106]
[0107] Table 7 shows that within the initial color range of ≤3000 times and COD ≤500 mg / L, the color removal rate can reach over 90%, and the COD removal rate can reach over 55%, indicating that the catalyst of this invention has good adaptability to palm oil wastewater with different water qualities. When the initial color exceeds 3000 times or the COD exceeds 500 mg / L, it is recommended to appropriately extend the reaction time or increase the catalyst / ozone dosage.
[0108] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a quaternary co-doped carbon-based catalyst of N, P, S, and Mn, characterized in that: Includes the following steps: (1) The porous carbon material was washed, dried, and calcined to obtain carbon precursor powder; (2) Dissolve the carbon precursor powder with nitrogen, phosphorus, sulfur and manganese sources in deionized water, disperse by ultrasonication and impregnate in water bath; (3) The mixture was subjected to a hydrothermal reaction and dried to obtain a precursor / carbon composite material; (4) The precursor / carbon composite material obtained in step (3) is calcined in an inert atmosphere, washed and dried to obtain a quaternary co-doped carbon-based catalyst.
2. The method for preparing the N, P, S, Mn quaternary co-doped carbon-based catalyst according to claim 1, characterized in that: In step (1), the porous carbon material is selected from one or more of coconut shells, hollow palm fruit bunches, straw, bamboo shavings, peanut shells, sugarcane bagasse, and sawdust.
3. The method for preparing the N, P, S, Mn quaternary co-doped carbon-based catalyst according to claim 1, characterized in that: In step (2), the nitrogen source is selected from one or more of urea, melamine, dicyandiamide, and ammonium nitrate; the phosphorus source is selected from one or more of phosphoric acid, phytic acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; the sulfur source is selected from one or more of thiourea, sodium thiosulfate, and benzenesulfonic acid; and the manganese source is selected from one or more of manganese nitrate, manganese acetate, manganese chloride, manganese sulfate, potassium permanganate, and manganese acetylacetone.
4. The method for preparing the N, P, S, Mn quaternary co-doped carbon-based catalyst according to claim 1, characterized in that: In step (2), the mass ratio of nitrogen source, phosphorus source, sulfur source and manganese source is 2~5:5~10:3~8:0.1~1.
5. The method for preparing the N, P, S, Mn quaternary co-doped carbon-based catalyst according to claim 1, characterized in that: In step (2), the water bath temperature is 50~70℃ and the time is 4~6h.
6. The method for preparing the N, P, S, Mn quaternary co-doped carbon-based catalyst according to claim 1, characterized in that: In step (3), the hydrothermal reaction temperature is 160~180℃ and the hydrothermal reaction time is 7~9h.
7. The method for preparing the N, P, S, Mn quaternary co-doped carbon-based catalyst according to claim 1, characterized in that: In step (4), the calcination temperature is 750~850℃, the heating rate is 5~8℃ / min, and the calcination time is 1.5~2.5h.
8. The N, P, S, Mn quaternary co-doped carbon-based catalyst prepared by the method described in any one of claims 1 to 7.
9. The application of the quaternary co-doped carbon-based catalyst according to claim 8 in the ozone catalytic oxidation deep decolorization treatment of palm oil wastewater.
10. The application according to claim 9, characterized in that: The catalyst dosage is 0.5~1.5 g / L, the ozone dosage is 50~150 mg / L, the reaction time is 30~90 min, and the reaction pH is 6.0~9.0.
Citation Information
Patent Citations
Preparation method of metal-doped carbon-nitrogen polymer-based self-cleaning film for in-situ oxidation pollution reduction and application device of metal-doped carbon-nitrogen polymer-based self-cleaning film
CN119869236A
Preparation method of heterogeneous catalyst, prepared catalyst and application
CN120885253A